Experimental Study of the Group Effect on the Bearing Capacity of Bored Piles in Sandy Soil - Melchior Filho, José (2020)
A foundation design must meet at least the following basic requirements: a) acceptable deformations under the working conditions; b) adequate safety against soil failure; and c) adequate safety against failure of structural elements. For the pile design, depending upon the spacing adopted among them, a pile may affect the other’s behavior. This occurs both in terms of bearing capacity and settlement. Researches on the group effect of bored piles in typical soils of Fortaleza (Northeast Brazil) is scarce, which justifies and motivates studies on the subject. The aim of the research reported here was to evaluate the group effect of bored piles in sandy soil, typical condition of the city of Fortaleza. An experimental campaign with 26 piles was performed on a site inside the campus of the Federal University of Ceará (Experimental Field of Geotechnics and Foundations of the Federal University of Ceará). The results of tests on single piles and groups were compared with estimations based on methods presented in the literature. The tested piles were observed to behave only by side friction, and group effect was noticed for all spacings investigated.